ALTERATION IN SOME BIOLOGICAL AND BIOCHEMICAL PARAMETERS IN TRIBOLIUM CASTANEUM (COLEOPTERA: TENEBRIONIDAE) DUE TO GARLIC OIL EFFECT - Beltagy, Bassiouni I.; Omar, Gehan A. (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
Over the centuries, man has struggled to protect his crops from invasion by insects, microbial pathogens and other pests. Stored grains of almost any kind are subjected to attack by insects, which are highly specialized and in most cases are of small size and have high reproductive potential, which make them easily concealed in grains and carried to many parts of the world. Once established in a commodity, they are usually difficult to control. The extensive and widespread use of synthetic insecticides during the past for the control has caused some concerns regarding the toxicity and environmental impact of these agents. Thus the present study was carried out to evaluate garlic oil as safe alternative to conventional insecticides and fumigants for the protection of wheat, as one of the important, grain products against Trobolium castaneum, as one of those serious stored products pests. Fourth larval instars of Tribolium castaneum, were reared on wheat treated with different concentration of the garlic oil (0.025, 0.1, 0.3, 0.6, 0.9, 1 ml/ 10gm of wheat) till adult emergence to study changes which could happen in its biological parameters. Also fourth larval instars reared on wheat treated with LC50, which found to be 0.49 ml, of the oil for two days to study some biochemical parameters, accordingly, the potential insecticidal properties of this oil could be assessed. The results show deleterious effects of garlic oil on the insect development and normal growth; as increasing rates of larval mortalities, extended larval and pupal durations, deformations of larvae shown in shrinking and c-shaped, significant decrease in pupation rate and of emerged adults. As for the biochemical studies; the protein content found to be increased as well alkaline phosphatase and cholinesterase activities, while glucose and lipid contents were decreased along with acid phosphatase, AST (aspartate aminotransferase) and ALT (alanine aminotransferase) activities, noticing that the decrease in AST was more than in ALT.